2021
DOI: 10.3390/ani11051257
|View full text |Cite
|
Sign up to set email alerts
|

Classical, Molecular, and Genomic Cytogenetics of the Pig, a Clinical Perspective

Abstract: The chromosomes of the domestic pig (Sus scrofa domesticus) are known to be prone to reciprocal chromosome translocations and other balanced chromosome rearrangements with concomitant fertility impairment of carriers. In response to the remarkable prevalence of chromosome rearrangements in swine herds, clinical cytogenetics laboratories have been established in several countries in order to screen young boars for chromosome rearrangements prior to service. At present, clinical cytogenetics laboratories typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 170 publications
0
8
0
Order By: Relevance
“…Conversely, numerical sex chromosome abnormalities are more tolerated by the species, because one of their X chromosomes is genetically inactivated [ 91 ], although some genes seem to escape gene inactivation [ 92 ]. However, numerical sex chromosome abnormalities are often correlated with sterility or low fertility, especially in females [ 3 , 4 , 5 , 6 , 7 ]. Balanced chromosomal abnormalities are generally correlated with reduced fertility due to unbalanced gametes originating during meiosis to form trivalent (centric fusions) or quadrivalent (reciprocal translocations) configurations.…”
Section: Clinical Cytogeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, numerical sex chromosome abnormalities are more tolerated by the species, because one of their X chromosomes is genetically inactivated [ 91 ], although some genes seem to escape gene inactivation [ 92 ]. However, numerical sex chromosome abnormalities are often correlated with sterility or low fertility, especially in females [ 3 , 4 , 5 , 6 , 7 ]. Balanced chromosomal abnormalities are generally correlated with reduced fertility due to unbalanced gametes originating during meiosis to form trivalent (centric fusions) or quadrivalent (reciprocal translocations) configurations.…”
Section: Clinical Cytogeneticsmentioning
confidence: 99%
“…Balanced chromosomal abnormalities are generally correlated with reduced fertility due to unbalanced gametes originating during meiosis to form trivalent (centric fusions) or quadrivalent (reciprocal translocations) configurations. Subsequently, unbalanced gametes and embryos generally die in early embryonic life [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Clinical Cytogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of reciprocal translocations are yet to be fully understood. However, recent studies suggest that the likelihood of translocations in the mammalian genome is associated with multiple chromosome features, such as physical length of chromosomes, frequency of translocation breakpoints, presence of common fragile sites, and chromatin density (e.g., heterochromatin or euchromatin) [8,10,[13][14][15][16][17][18][19]. In a recent study, Donaldson et al [20] reported a significant association of translocation frequency to the length of chromosome arms where larger chromosome arms tend to possess more translocation breakpoints.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, more than 200 reciprocal translocations have been identified genome-wide, which cause a reduction in litter size up to 50% due to high mortality among early em-bryos [3,8,9]. Published data showed that approximately 50% of boars have hypoprolificacy due to reciprocal translocation with normal semen parameters [9,10]. Reciprocal translocations are heritable and can occur de novo, and do not appear to be line-specific.…”
Section: Introductionmentioning
confidence: 99%